2012
DOI: 10.1364/oe.20.019297
|View full text |Cite
|
Sign up to set email alerts
|

Beaming circularly polarized photons from quantum dots coupled with plasmonic spiral antenna

Abstract: Coupling nanoscale emitters via optical antennas enables comprehensive control of photon emission in terms of intensity, directivity and polarization. In this work we report highly directional emission of circularly polarized photons from quantum dots coupled to a spiral optical antenna. The structural chirality of the spiral antenna imprints spin state to the emitted photons. Experimental results reveal that a circular polarization extinction ratio of 10 is obtainable. Furthermore, increasing the number of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Efforts have been made to modulate the fluorescence emission direction. For example, optical nanoantennas made of metallic nano-structures have been used to beam the fluorescence emission from the fluorescent quantum dots which are within near-field distances from the antenna [2,3]. Gold nano-apertures surrounded by periodic corrugations were used to transform standard fluorescent molecules into bright unidirectional sources [4].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to modulate the fluorescence emission direction. For example, optical nanoantennas made of metallic nano-structures have been used to beam the fluorescence emission from the fluorescent quantum dots which are within near-field distances from the antenna [2,3]. Gold nano-apertures surrounded by periodic corrugations were used to transform standard fluorescent molecules into bright unidirectional sources [4].…”
Section: Introductionmentioning
confidence: 99%
“…In radiofrequency antenna engineering, it is well known that right hand or left hand circular polarization (RHC and LHC) can be transmitted with spiral antenna with different handedness [40]. It has been demonstrated that it is feasible to construct a nanoscale circularly polarized photon source with unidirectional emission through coupling an electric dipole emitter to a spiral plasmonic antenna [41,42]. The polarization of the emitted photon arises from the structural handedness of the spiral antenna that converts the electric dipole emission into far field.…”
Section: Beaming Photons With Spin and Orbital Angular Momentummentioning
confidence: 99%
“…However, for the circular polarization illumination model, structural geometrical features must be improved to match the excited phases because SPPs can only be generated only when the incident light polarization is perpendicular to the slit [19]. From then on, the geometric phase effect of the archimedean spiral slit has been used to focuse SPPs at irradiations with the left-hand and right-hand circular polarizations into spatially separated plasmonic fields [20], thereby generating circularly polarized vortex emission [21], [22], and miniaturizing the circular polarization analyzer [23]- [25]. Recently, nanostructures composed of subwavelength apertures have been designed to tune SPPs excited by light with circular polarization [19].…”
Section: Introductionmentioning
confidence: 99%